Terapi Aktivitas Kelompok dengan Terapi Butterfly Hug Terhadap Tingkat Kecemasan Lansia di Panti Werdha Kasih Ayah Bunda - Ameliani, Indri; Siti Robeatul Adawiyah; Adilah Salsabila; Ahmad Kurtusi; Aninda Rizki Maulida; Anis Nurfaidah; Anisa; Dida Ningtias; Dita Faradillah; Dwi Sinta (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The elderly are individuals who have entered the age of 60 years and above. The World Health Organization (WHO) classifies the elderly in several categories: middle age (45-59 years), elderly (60-74 years), elderly (75-90 years), and very old age (90 years). As they age, the elderly are more prone to experiencing anxiety disorders that can impact their quality of life. Objective: The purpose of Butterfly Hug Group Activity Therapy is to reduce anxiety in the elderly. Method: This group activity therapy has 3 stages, namely the orientation stage, the work stage with the administration of butterfly hug therapy, and the termination stage. Result: The population in this activity was the elderly totaling 13 people by distributing the "Hamilton Anxiety Rating Scale (HARS)" pre-test and post-test anxiety level questionnaires. The results of the pre-test questionnaire before therapy were obtained by 4 elderly people with moderate anxiety, 8 elderly people experienced mild anxiety, and 1 elderly person had no anxiety. Meanwhile, the post-test results after butterfly hug therapy were obtained, 1 elderly person experienced mild anxiety and 12 elderly people had no anxiety. Conclusion: Butterfly Hug therapy can provide positive benefits for the elderly who have been intervened such as, reducing anxiety and anxiety, improving comfort, and improving sleep quality. For the elderly, it also helps reduce mind distractions and improves the ability to focus and concentrate.